Peningkatan Mutu Pembelajaran melalui Manajemen Berbasis Sekolah di SMP Negeri Kur Selatan Kota Tual - Abdul Rahim Letsoin (Journal on Education, 2025)
This research aims to determine the implementation of school-based management in improving the quality of learning in the Kur state junior high school, Kur Selatan sub-district, Tual city. The method used is descriptive qualitative research. Data sources, primary, secondary. Collection techniques, observation, interviews, documentation. Data analysis techniques: reduction, presentation, verification. The results of the research show that management by the school principal is quite good. From the aspect of learning planning in accordance with semester programs, annual programs, improving the quality of teacher performance, learning quality both in class management and learning media users, and evaluations carried out by the school principal. There are still limited teachers for several subjects, English, Mathematics, Physics. Very limited facilities and infrastructure which are not commensurate with the number of students. Limited learning media, geographical location factors, lack of continuous regional government attention, lack of good evaluation and monitoring factors by the Tual City Education Office.